THE AVAILABILITY OF THE ELEMENTS FOR USING ACTIVITY-BASED COST ACCOUNTING (ABC) IN COMMERCIAL BANKS OPERATING IN THE IRAQI STOCK EXCHANGE - Abbas Fadel Chiyad (Scholars Digest Publishing, 2024)
This study aimed to determine the possibility of applying the activity-based cost accounting system (ABC) in the environment of commercial banks operating in the Iraqi Stock Exchange. This was tested through a main hypothesis that commercial banks have the basic components that enable them to apply the cost accounting system. On the basis of activities (ABC), which represents the dependent variable in the study. The study included a theoretical aspect of knowing the elements of costs, the theories of costs, the feasibility of their application and the methods of calculating and charging them, whether direct or indirect. On the practical side, the researcher relied on a questionnaire form distributed to the study community of all commercial banks operating on Iraq's stock market. The study concluded several results, the most important of which is the ability of the cost accounting system to provide more accurate and clear information about the banking services provided to customers, as well as benefiting from that system in processes related to planning, organization, auditing and control, improving management decisions, and increasing effectiveness and economic efficiency in commercial banks operating in the Iraqi Stock Exchange. Based on the results of the study, the study recommended using the activity-based cost accounting system (ABC), which leads to providing more useful data and information to all users at a lower cost and with high accuracy, and gradually moving in stages from a specific department to the rest of the departments at the bank level as a whole.
Keywords: Activity-based cost accounting, Commercial banks, Iraq stock market, accounting information, Users of financial statements.